2018
DOI: 10.1002/qua.25806
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical computational study of oxygen vacancies in a decahedral anatase nanoparticle

Abstract: Formation of oxygen vacancies (VO) is an important step of many catalytic reactions following the Mars van Krevelen mechanism. High rate of oxidation is associated with low energy of VO formation while high selectivity requires an optimal energy of VO formation. In the present computational study, enthalpy of VO formation (ΔHOVF) is studied in a decahedral anatase nanoparticle (TiO2)121(H2O)6 using PM6 method. ΔHOVF shows large variations for oxygen atoms in different locations on facets, edges and vertices. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Le and Schweigert investigated the interfaces between two decahedral anatase nanoparticles of (TiO 2 ) 70 (H 2 O) 2 connected together via their (001) facets or via (101) facets [21]. They found that the deep trap states could be localized at the interfaces between two nanoparticles due to local structure deformations.…”
Section: The Structure Of the Surfaces Of Tio2 Nanoparticlesmentioning
confidence: 99%
“…Le and Schweigert investigated the interfaces between two decahedral anatase nanoparticles of (TiO 2 ) 70 (H 2 O) 2 connected together via their (001) facets or via (101) facets [21]. They found that the deep trap states could be localized at the interfaces between two nanoparticles due to local structure deformations.…”
Section: The Structure Of the Surfaces Of Tio2 Nanoparticlesmentioning
confidence: 99%